THE ROLE OF NEP 2020 IN SHAPING CONSUMER SKILLS AND BEHAVIORAL TRENDS IN INDIA'S EVOLVING MARKET - Dr. Suchithra Devi S 1, Aswathy Chandra C H 2, Pujari Jhansi laxmi 3, Mr. Lakshmana Rao 4, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
India's educational system is set to undergo a dramatic change with the implementation of the National Education Policy 2020 (NEP 2020), which would have a profound impact on a number of areas, including market dynamics and consumer behaviour. This article examines how NEP 2020 can affect consumer behaviour and skill developments in India's changing market. We investigate how the focus on digital literacy, critical thinking, and vocational skills in NEP 2020 may affect consumer decision-making processes, financial literacy, and overall market engagement through a thorough assessment of the literature and consideration of policy objectives. The research underscores the possibility of heightened consumer consciousness, better-informed buying choices, and a transition towards sustainable consumption habits. It also looks into how technology integration in the classroom influences the uptake of e-commerce and digital consumption. Using a mixed-methods approach, the study combines consumer surveys, expert interviews, and policy analysis. According to research, NEP 2020 may result in a customer population that is more astute and powerful, which might change consumer desires and corporate tactics in India. The ramifications for corporations, legislators, and educators in anticipating and adjusting to these shifts in consumer behaviour are covered in the article's conclusion.